An injectable multifunctional nanocomposite hydrogel promotes vascularized bone regeneration by regulating macrophages - Huaiyuan Zhang; Yu Wang; Wenyu Qiao; Xueneng Hu; Huifen Qiang; Kuo Xia; Longhai Du; Luling Yang; Yi Bao; Jie Gao; Tinglin Zhang; Zuochong Yu (Journal of Nanobiotechnology)
Abstract The local inflammatory microenvironment, insufficient vascularization, and inadequate bone repair materials are the three key factors that constrain the repair of bone defects. Here, we synthesized a composite nanoparticle, TPQ (TCP-PDA-QK), with a core‒shell structure. The core consists of nanotricalcium phosphate (TCP), and the shell is derived from polydopamine (PDA). The surface of the shell is modified with a vascular endothelial growth factor (VEGF) mimic peptide (QK peptide). TPQ was then embedded in porous methacrylate gelatin (GelMA) to form a TPQGel hydrogel. In the inflammatory environment, the TPQGel hydrogel can gradually release drugs through pH responsiveness, promoting M2 macrophage polarization, vascularization and bone regeneration in turn. In addition, reprogrammed M2 macrophages stimulate the generation of anti-inflammatory and pro-healing growth factors, which provide additional support for angiogenesis and bone regeneration. The TPQGel hydrogel can not only accurately fill irregular bone defects but also has excellent biocompatibility, making it highly suitable for the minimally invasive treatment of bone defects. Transcriptomic tests revealed that the TPQGel hydrogel achieved macrophage reprogramming by regulating the PI3K-AKT signalling pathway. Overall, the TPQGel hydrogel can be harnessed for safe and efficient therapeutics that accelerate the repair of bone defects. Graphical Abstract